Valorization of Cultural Heritage in the Promotion of Education for Sustainable Development: Analysis of the Cultural Site Hill of Ambohimanga, Analamanga Region, Madagascar - Andrianaivo Onja Linà; Rasamimanana Hantanirina; Andrianarimanana Jean Claude Omer; Rabotovao Sylvain; Andrianjary Myriam; Razanadrasoa Vololonome Bodomalala; Rakotoson Olivia; Ratiarimananjatovo Narindra; Ratsimandisa Haritiana Zo; Koto-Te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina Baholy (Lakhomi Journal Scientific Journal of Culture, 2024)
International and national entities like UNESCO, the Malagasy Cultural Heritage Policy Framework (CPPC), and the Malagasy Ministry of Culture and Communication (MCC) advocate for leveraging cultural heritage as a significant catalyst for sustainable development. They acknowledge the historical, cultural, environmental, and touristic wealth intertwined with cultural heritage within the framework of Education for Sustainable Development (ESD) for the populace. This study aims to illustrate how cultural heritage can genuinely contribute to enhancing and advancing education towards sustainable development. It scrutinizes the potential correlation between artifacts and heritage assets of cultural sites and the socio-cultural, environmental, and economic facets of sustainable development, with a focal point on the Ambohimanga hill in the Analamanga region. Findings reveal that cultural sites embody traits that align with the goals of ESD, via their tangible and intangible heritage assets. They facilitate a heightened consciousness of our lineage and our cultural and social identity, thereby ensuring the perpetuation of our heritage for posterity. Moreover, they play a role in conserving the environment and biodiversity by housing endemic and medicinal fauna and flora, thus safeguarding their existence for future generations. Furthermore, they spur local and national economic growth by drawing tourists, generating revenue, and fostering employment opportunities. Propagating education about cultural heritage through cultural site visits presents a promising avenue as a component of ESD.